Patient motivators to use opioids for acute pain after emergency care - Punches, Brittany E.; Brown, Jennifer L.; Taul, Natalie K.; Sall, Hawa A.; Bakas, Tamilyn; Gillespie, Gordon L.; Martin-Boone, Jill E.; Boyer, Edward W.; Lyons, Michael S. (Frontiers in Pain Research, 2023)
Introduction Patients are stakeholders in their own pain management. Factors motivating individuals to seek or use opioids therapeutically for treatment of acute pain are not well characterized but could be targeted to reduce incident iatrogenic opioid use disorder (OUD). Emergency departments (EDs) commonly encounter patients in acute pain for whom decisions regarding opioid therapy are required. Decision-making is necessarily challenged in episodic, unscheduled care settings given time pressure, limited information, and lack of pre-existing patient provider relationship. Patients may decline to take prescribed opioids or conversely seek opioids from other providers or non-medical sources. Methods Using a framework analysis approach, we qualitatively analyzed transcripts from 29 patients after discharge from an ED visit for acute pain at a large, urban, academic hospital in the midwestern United States to describe motivating factors influencing patient decisions regarding opioid use for acute pain. A semi-structured interview guide framed participant discussion in either a focus group or interview transcribed and analyzed with conventional content analysis. Results Four major themes emerged from our analysis including a) pain management literacy, b) control preferences, c) risk tolerance, and d) cues to action. Discussion Our findings suggest targets for future intervention development and a framework to guide the engagement of patients as stakeholders in their own acute pain management.